The safety profile of a protocolized transbronchial cryobiopsy program utilizing a 2.4 mm cryoprobe for interstitial lung disease. (August 2022) - Oh, Scott; Ronaghi, Reza; He, Tao; Oberg, Catherine; Channick, Colleen; Susanto, Irawan; Carroll, Mathew; Weigt, S Sam; Sayah, David; Dolinay, Tamas; Chung, Augustine; Fishbein, Gregory; et al.
Abstract: Introduction: Transbronchial lung cryobiopsy (TBLC) has emerged as a promising alternative to surgical lung biopsy for the diagnosis of interstitial lung disease. However, uncertainty remains regarding its overall complications due to a lack of procedural standardization including the size of cryoprobe utilized. Methods: This is a prospective cohort study of a protocolized transbronchial cryobiopsy program utilizing a 2.4 mm cryoprobe. 201 consecutive subjects were enrolled at a single academic center. Results: The average biopsy size was 106.2 ± 39.3 mm 2 . Complications included a total pneumothorax rate of 4.9% with 3.5% undergoing chest tube placement. Severe bleeding defined by the Nashville Working Group occurred in 0.5% of cases. There were no deaths at 30-days. Discussion: A protocolized transbronchial cryobiopsy program utilizing a 2.4 mm cryoprobe in can achieve a high diagnostic yield with a favorable safety profile. Highlights: This paper looks at the safety and outcomes for cryobiopsy for diffuse parenchymal lung disease. We believe this paper would add a good support for the use of cryobiopsy in the diagnosis of interstitial lung disease and its safety profile. We highlight our experience with our protocol with the 2.4 mm cryoprobe and its safety profile and diagnostic yield.